2016
DOI: 10.4238/gmr.15027968
|View full text |Cite
|
Sign up to set email alerts
|

Altered callose deposition during embryo sac formation of multi-pistil mutant (mp1) in Medicago sativa

Abstract: ABSTRACT. Whether callose deposition is the cause or result of ovule sterility in Medicago sativa remains controversial, because it is unclear when and where changes in callose deposition and dissolution occur during fertile and sterile embryo sac formation. Here, alfalfa spontaneous multi-pistil mutant (mp1) and wild-type plants were used to compare the dynamics of callose deposition during embryo sac formation using microscopy. The results showed that both mutant and wild-type plants experienced megasporogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Callose is a cell wall β‐1,3‐glucan polymer that plays an essential role in plant reproductive processes such as megasporogenesis (Newbigin et al, 2009; Zhou, 2019). It is also involved in pollen–pistil interactions in plants, acting as a marker for abnormal ovule development and affecting micropylar PT guidance (Zhou et al, 2016). The callose accumulation observed in the reciprocal crosses between galt25789 pistils and WT PGs (22%) indicates a defect of female origin.…”
Section: Discussionmentioning
confidence: 99%
“…Callose is a cell wall β‐1,3‐glucan polymer that plays an essential role in plant reproductive processes such as megasporogenesis (Newbigin et al, 2009; Zhou, 2019). It is also involved in pollen–pistil interactions in plants, acting as a marker for abnormal ovule development and affecting micropylar PT guidance (Zhou et al, 2016). The callose accumulation observed in the reciprocal crosses between galt25789 pistils and WT PGs (22%) indicates a defect of female origin.…”
Section: Discussionmentioning
confidence: 99%
“…While pollen tube germination and growth along the transmitting tract was wild-type-like in the mutant, our results showed that the concomitant loss of both, AtLTP1.4 and AtLTP1.8 gene functions, caused aberrant callose deposition patterns in the ltp1.4/1.8 mutant ovules. Callose represents a cell wall β-1,3-glucan polymer and alike for other angiosperms, in wild-type Arabidopsis plants plays an essential role during megasporogenesis (Newbigin et al, 2009; Zhou et al, 2016) of female reproductive development. Typically, callose deposition is first observed in the wall of the megasporocyte, and after meiosis in the walls of the megaspore tetrad (Schneitz et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Among the floral organs, the pistil has the most complex structure, and its reproductive growth and development processes are regulated by a large number of transcription factors and functional genes [5][6][7]. Several genes regulating pistil development and physiological and biochemical changes during pistil abortion have been identified through mapping and cloning of female sterile mutant genes in Arabidopsis thaliana, rice, cotton, maize, and rapeseed, leading to a gradual understanding of the morphological model and genetic regulation of pistil development [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%